2020
DOI: 10.3389/fpsyg.2019.02954
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of a Conductor Competition for the Study of Emotional Synchronization Within and Between Groups in a Natural Musical Setting

Abstract: Group emotional dynamics are a central concern in the study of human interaction and communication. To study group emotions, the social context of a musical event in natural conditions may overcome several limits of laboratory experiments and could provide a suitable framework. This study aimed to evaluate if cultural events such as a conductor competition could welcome scientific research for the study of group emotional sharing. We led an observational study, which suggests that in this particular context, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…This work is a first step for the study of musical chills using EEG in more ecological paradigms. In future experiments, with the development of wireless mobile EEG systems and coupled with physiological measures, EEG recordings characterizing musical pleasure and musical chills in both social contexts and live conditions would provide a relevant parameter to study emotional synchronization of groups (Chabin et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This work is a first step for the study of musical chills using EEG in more ecological paradigms. In future experiments, with the development of wireless mobile EEG systems and coupled with physiological measures, EEG recordings characterizing musical pleasure and musical chills in both social contexts and live conditions would provide a relevant parameter to study emotional synchronization of groups (Chabin et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…With the development of wireless headsets, fast and easy handling headsets, new perspectives are open for the study of social and affective neurosciences in multi-subject paradigms [ 68 ] in natural or ecological musical settings. The study of group dynamics both with subjective responses and objective neurophysiological devices would provide relevant and as-yet-unknown data about cerebral processing associated with behavior and even feeling/emotions [ 34 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the cerebral synchronization of multiple people in the context of music emotion has never been investigated, and its study should lead to progress in understanding group emotional dynamics. Recording the cerebral activity of several people simultaneously in a natural setting while they are listening to emotional music should partially cover this gap [ 34 ], despite being a very challenging prospect. A previous study assessed the feasibility of such a paradigm in a concert [ 34 ] and suggested a good adherence of the majority of public participants and musicians.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations